Peculiarities of teaching the theme «TV Journalism» on the example of the channel «Culture» (Russia) for students non-core specialties - Fedorova Н.В. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
The article reveals the results of experimental work on solving the problem of presenting cultural achievements in television media in the classroom for students of the areas of «socio-cultural activity», «folk art culture» and «library and information activities.» The analysis for students is based on the Russian state television channel “Culture” with its programs reflecting different directions in the cultural life of Russia and the world. The paper presents the results of a survey of students on the problem of watching television channels and individual television shows. The features of the training course for non-core (humanitarian) specialties and conducting classes on the topic «Television Journalism», devoted to acquaintance with the best television broadcasts on culture on Russian television channels, are disclosed. The author describes the stages of the preparation of presentations by students and the analysis of video clips of television programs, draws conclusions about the knowledge and skills received by students on the subject based on the proposed methodology